Search for B+→X(3872)K+, X(3872)→J/ψγ - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2006)
In a study of B+→J/ψγK+ decays, we find evidence for the radiative decay X(3872)→J/ψγ with a statistical significance of 3.4σ. We measure the product of branching fractions B(B+→X(3872)K+) •B(X(3872)→J/ψγ)=(3.3±1.0±0.3)×10-6, where the uncertainties are statistical and systematic, respectively. We also measure the branching fraction B(B+→χc1K+)=(4.9±0.2±0.4) ×10-4. These results are obtained from (287±3) million BB̄ decays collected at the Υ(4S) resonance with the BABAR detector at the PEP-II B Factory at SLAC. © 2006 The American Physical Society.